Fonclaire South Pan Champs: Skiffle Bunch in Third Place. - Webb, Yvonne (Trinidad Guardian)
Not yet recovered from being denied an opportunity to play in the National Panorama finals, TCL Group Skiffle Bunch was dealt another blow when the band was relegated to third place at the South/Central Regional Panorama competition at Skinner Park. While Fonclaire took the top stop with 257 points.
Keywords: Steel bands (Music) -- Competitions -- Trinidad and Tobago; Steel band music -- Trinidad and Tobago; Panorama (Musical festival)